ANALISIS PROKSIMAT DAN SIFAT ORGANOLEPTIK “ONCOM MERAH ALTERNATIF” DAN “ONCOM HITAM ALTERNATIF” - Sri Mulyani; Restu Widyana Wisma (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2016)
Oncom is a typical food of the people of West Java. So far there are two types of oncom known, namely red oncom and black oncom. Red oncom is generally made from tofu cake (soybean that has been taken protein in making tofu) with mold Neurospora sitophila. While black oncom is generally made from peanut cake which is sometimes mixed with tapioca flour with Rhizopus oligosporus tempeh mold. This research was conducted to utilize a mixture of tofu waste (ampas), tapioca waste (onggok) and peanut oil waste (bungkil) which is widely distributed in West Java to be processed into a type of oncom food so that it can be utilized. Because the raw material and composition used in this study are different from red oncom and black oncom in general, they are called "alternatif red oncom" and "alternatif black oncom". This study aims to analyze the proximate specifically the protein and fat content, as well as the organoleptic properties of "alternatif red oncom" and "alternatif black oncom". This study was conducted with experiments in the laboratory and the data were analyzed using descriptive statistical methods. The research was begun by making oncom from raw materials mixture of the tofu waste (ampas), onggok, and bungkil, then fermented with N. sitophila microbes for "alternatif red oncom" and R. oligosporus for "alternatif black oncom". After the oncoms were formed, the protein content was tested using the Kjeldahl method and fat content using the Soxhlet method. Organoleptic test of oncom products before and after being processed into food is carried out by the Hedonic test. The results showed that the protein content of "alternatif red oncom" (2.78 ± 0.05 %) is higher than "alternatif black oncom" (1.88 ± 0.05 %), and the fat content in "alternatif red oncom" (2.31 ± 0.05 %) is higher than "alternatif black oncom" (1.90 ± 0.05 %). The organoleptic test results showed that in terms of color, aroma, and texture "alternatif black oncom" tends to be preferred by panelists than "alternatif red oncom".